2003
DOI: 10.1002/ptr.1268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diuretic activity of the constituents of Clematis montevidensis Spreng. (Ranunculaceae) in rats

Abstract: The effects of Clematis montevidensis Spreng. (Ranunculaceae) on urinary excretion of water, sodium and potassium were investigated in rats loaded with isotonic saline solution. The data reported in the present work indicate that the infusions of the root and aerial part of Clematis montevidensis showed a moderate diuretic activity. This effect could be due, at least in part, to the presence of oleanolic acid isolated from this plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Leaf extracts evoked no changes in diuresis or natriuresis. Whether their actives have diuretic effects need further attention (i.e., oleanolic acid, Alvarez et al, 2002Alvarez et al, , 2003Somova et al, 2003 andpolyphenols, Singh et al, 2007). Studies should also address the effect of differing doses.…”
Section: Diuretic Activitymentioning
confidence: 98%
“…Leaf extracts evoked no changes in diuresis or natriuresis. Whether their actives have diuretic effects need further attention (i.e., oleanolic acid, Alvarez et al, 2002Alvarez et al, , 2003Somova et al, 2003 andpolyphenols, Singh et al, 2007). Studies should also address the effect of differing doses.…”
Section: Diuretic Activitymentioning
confidence: 98%
“…The dry roots have long been used in traditional Chinese medicine to treat rheumatic diseases and to alleviate pain (Mimaki et al, 2004). Accumulative evidence has demonstrated that many plants from Clematis species possess antitumor, antimicrobial, antifungal, antiinfl ammatory and diuretic activities (Mimaki et al, 2004;Zhao et al, 2005;Khan et al, 2001;Buzzini and Pieroni, 2003;Kim et al, 2005a;Park et al, 2006;Li et al, 2006;Alvarez et al, 2003) and triterpenoid saponins may be the main active components (Mimaki et al, 2004). Recently, C. manshurica Rupr., a congeneric plant of C. chinensis, has been shown to have chondroprotective effects in vitro and in vivo (Choi et al, 2002;Kim et al, 2005b;Lee et al, 2005Lee et al, , 2007Hartog et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The oleanolic acid is a bioactive pentacyclic triterpene, and several studies report the antioxidant, antibacterial, antiinflammatory, anti-HIV, hepatoprotective and diuretic activity of this compound (Zhou et al, 2011;Li et al, 2002). The presence of oleanolic acid has also been associated to the diuretic activity of Fabiana patagonica (Solanaceae) (Alvarez et al, 2003) and Viscum angulatum (Viscaceae) (Jadhav et al, 2010); however, it is reported that this compound induces diuresis with a significant loss of potassium (Jadhav et al, 2010). Interestingly, in our study, the HEPG presented an important potassium and chloride-sparing effect, suggesting that the oleanolic acid found in Pereskia grandifolia may probably act in synergy with other metabolites of the extract that modulate its diuretic effect.…”
Section: Discussionmentioning
confidence: 96%